Numerical Modeling of an Umbrella-Shaped Bolt and Its Anchorage Characteristics in Rock Engineering - Xiong, Yong; Chen, Hang; Cheng, Yonghui; Hu, Shenggang; Wang, Zhaofeng; Gao, Yaohui (Frontiers in Earth Science, 2022)
The umbrella-shaped bolt (U-bolt) is a novel type of mechanical bolt used for rock reinforcement. It is made of a smooth steel bar, hinges, rigid rods, and sliding blocks. During installation and operation, the tension of the bolt is converted into the extrusion force on the rock mass deep in slope, so that the higher compressive strength of the rock mass is used to obtain the greater friction force and anchoring force. In this article, the structural and mechanical analysis results of the U-bolt is provided, and the relation between penetration and point normal stress is discussed. Based on these analyses, a simulation method for the U-bolt is proposed. The bolt elements are identified at first, then the penetration on the rock mass is calculated, and the tensile strength of bolt elements is increased to a reasonable value. Meanwhile, the method is applied to deep-buried rock reinforcement and a rock slope, and simulation results reveal that the U-bolt can alleviate the fracturing degree and reduce the depth and displacement of the excavation damaged zone (EDZ), and decrease the landslide distance.